The kynurenine and serotonin pathway, neopterin and biopterin in depressed children and adolescents: an impact of omega-3 fatty acids, and association with markers related to depressive disorder. A randomized, blinded, prospective study - Ilavská, Lucia; Morvová, Marcela; Paduchová, Zuzana; Muchová, Jana; Garaiova, Iveta; Ďuračková, Zdenka; Šikurová, Libuša; Trebatická, Jana (Frontiers in Psychiatry, 2024)
Depressive disorder is a severe mental condition. In addition to genetic factors, immunologicalinflammatory factors, oxidative stress, and disturbances in neurotransmitter metabolism, kynurenine and serotonin pathways may play a role. The exact mechanisms, especially in depressed children and adolescents, are not fully understood. Our primary hypothesis was whether the metabolites of tryptophan degradation in children and adolescents with depressive disorder might be influenced by omega-3 FAs compared to omega-6 FAs during a 12-week supplementation. A secondary hypothesis was to investigate whether tryptophan metabolites in children and adolescents are associated with markers of inflammatory response, oxidative stress, cortisol, and the serum omega-6/omega-3 FA ratio. Metabolites of tryptophan degradation and pteridines, neopterin, and biopterin in urine were analyzed with an HPLC system. Surprisingly, omega-3 FAs stimulated both kynurenine (kynurenine/tryptophan ratio) and serotonin (5-hydroxytryptophan) pathways, whereas omega-6 FAs only increased the kynurenine/tryptophan ratio. Neopterin and biopterin were not different from the healthy controls. Biopterin increased after omega-3 FA supplementation. Serotonin was positively correlated with lipoperoxidation and a marker of oxidative protein damage. Of the monitored tryptophan metabolites, only 5-hydroxyindolacetic acid was positively correlated with the severity of depression, total cholesterol, and negatively with brain-derived neurotrophic factor and glutathione peroxidase. In conclusion, in children and adolescents, both supplemented FAs stimulated the kynurenine pathway (kynurenine/tryptophan ratio) and kynurenine formation. However, the serotonin pathway (5-hydroxytryptophan) was stimulated only by omega-3 FA. Tryptophan metabolism is associated with oxidative stress, inflammation, total cholesterol, and cortisol. We are the first to point out the association between the kynurenine pathway (KYN/TRP ratio) and the omega-6/omega-3 FA ratio. The metabolite 5-HIAA could play a role in the pathophysiology of depressive disorder in children and adolescents. Project registration: ISRCTN81655012